2007
DOI: 10.1002/art.22899
|View full text |Cite
|
Sign up to set email alerts
|

Test–retest reliability of the peak knee adduction moment during walking in patients with medial compartment knee osteoarthritis

Abstract: Objective. To estimate the test-retest reliability of the peak external knee adduction moment during walking in patients with medial compartment knee osteoarthritis (OA), and to describe the interpretation of the reported values. Methods. A total of 31 patients diagnosed with knee OA confined primarily to the medial compartment underwent quantitative gait analyses during 2 separate test sessions at least 24 hours apart and within 1 week. The peak knee adduction moment was calculated for each patient at each se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
96
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 142 publications
(106 citation statements)
references
References 44 publications
7
96
0
3
Order By: Relevance
“…The variable of most interest is the external knee adduction moment (KAM), which acts to rotate the tibia in a varus direction. The external KAM is a reliable and valid indicator of medial knee load (11,12) and is most often quantified by evaluating the 2 peaks during stance, as well as the impulse (area under the KAM-time curve). The first and typically largest peak occurs during the load acceptance phase of gait (approximately 25% stance), and the second peak occurs during the propulsion phase (approximately 75% stance) (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…The variable of most interest is the external knee adduction moment (KAM), which acts to rotate the tibia in a varus direction. The external KAM is a reliable and valid indicator of medial knee load (11,12) and is most often quantified by evaluating the 2 peaks during stance, as well as the impulse (area under the KAM-time curve). The first and typically largest peak occurs during the load acceptance phase of gait (approximately 25% stance), and the second peak occurs during the propulsion phase (approximately 75% stance) (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…26 Two participants actually exhibited less knee extension after the tibiofemoral glide. One of these participants was the oldest in the group, and the other had had the most recent surgery.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have proven the validity of KAM for prediction of clinical and radiological osteoarthritis progression. 6 Orthotic treatment can alter loading to the knee in the hope of reducing symptoms and disease progression. Biomechanical studies have demonstrated a small effect size in reduction of KAM with a valgus knee brace [7][8][9][10] and lateral-wedged insoles.…”
Section: Discussionmentioning
confidence: 99%